Avaliação do papel da obesidade e de adipocinas como fatores de risco de Tromboembolismo Venoso: um estudo de casocontrole - Pinheiro, Patricia Nunes Bezerra [UNIFESP] (2019)
Introduction: The venous thromboembolism (VTE) is a frequent disease related to a relevant morbimortality. The association between obesity and VTE is particularly important due the increased prevalence of obesity in the world. The mechanism that obesity increases the risk of VTE is multifactorial, related probably to the venous stasis, low grade of inflammation, hypercoagulability and hypofibrinolysis. Altering the levels of some adipokines, such as leptin and adiponectin, may be relevant in the mechanism of VTE, as they are able to influence hemostasis. Studies exploring the role of adipokines in the thrombotic risk may contribute to a better understanding of pathophysiology of VTE in obesity. Purpose: To investigate the effect of anthropometric measurements of obesity (body mass index – BMI, waist circumference, hip circumference and hip waist ratio) and the levels of leptin and adiponectin in the risk of VTE. In patients and controls, the relationship between obesity measures and leptin and adiponectin levels, and the correlation of levels of these adipokines with several factors of hemostasis, adhesion molecules and Creactive protein (CRP) were evaluated. Methods: We conducted a case-control study with 85 patients, aged 18-60 years, with a single event of VTE and 120 controls. Patients and controls were matched according to sex and age (± 5 years). Results: The obesity measures were associated with VTE risk, even after the adjusting for potential confounding factors (age, sex, ethnicity, schooling and estrogen use). For example, the BMI ≥30 kg/m2 increased the risk of VTE (Odds ratio 2.33; CI 95% 1.08- 5.01) by approximately 2.5 times the reference (BMI 18.5-24.9 kg/m2). There was no association between leptin or adiponectin levels and thrombotic risk when evaluated as tertiles or continuous variables. Obesity measures positively associated with the leptin levels and negatively with the adiponectin levels in patients and controls. The correlations were weak or absent between levels of adipokines and levels of factors of hemostasis, adhesion molecules and CRP. Conclusions: As expected, obesity was associated with an increased risk of VTE. There was no contribution of leptin or adiponectin levels to the risk of VTE. However, the present results may be used as a source for prospective studies, with larger sample size, and aimed to elucidate the role of adipokines in the risk of VTE.